2006
DOI: 10.1016/j.pain.2005.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic nonmalignant pain on highway driving performance

Abstract: Most pain patients are treated in an outpatient setting and are engaged in daily activities including driving. Since several studies showed that cognitive functioning may be impaired in chronic nonmalignant pain, the question arises whether or not chronic nonmalignant pain affects driving performance. Therefore, the objective of the present study was to determine the effects of chronic nonmalignant pain on actual highway driving performance during normal traffic. Fourteen patients with chronic nonmalignant pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
57
1
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 31 publications
3
57
1
6
Order By: Relevance
“…Whilst there has been much research into the effects of opioids on memory, methodological difficulties mean that it is difficult to generalise many of the findings. The use of comparison groups is problematic, as pain itself can have effects on cognitive functioning (Veldhuijzen et al 2006) and it can also modulate the side effects of opioids (Borgberg et al 1996). Kamboj et al used a relatively brief test battery so as not to unduly tire or stress the patients who participated in the study and so were unable to discern which specific processes of memory contributed to the amnestic effects observed.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst there has been much research into the effects of opioids on memory, methodological difficulties mean that it is difficult to generalise many of the findings. The use of comparison groups is problematic, as pain itself can have effects on cognitive functioning (Veldhuijzen et al 2006) and it can also modulate the side effects of opioids (Borgberg et al 1996). Kamboj et al used a relatively brief test battery so as not to unduly tire or stress the patients who participated in the study and so were unable to discern which specific processes of memory contributed to the amnestic effects observed.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Veldhuijzen ve ark. [6] kronik kanser dışı ağrısı olan hastaların otoyolda araba kullanma performanslarını değerlendirdikleri çalış-mada, ağrısı olan olguların performanslarını kontrol grubuna göre kötü bulmuşlardır. Aynı şekilde Kuhajda ve ark.…”
Section: Discussionunclassified
“…Despite its clinical usefulness, some studies have reported negative effects on learning and memory, but these impairments are difficult to dissociate from the effects of previous/concurrent drug abuse, physical correlates of substance dependence (e.g., withdrawal, pain, trauma, blood-born infectious diseases), and disadvantaged social context (Darke et al 2000;Davis et al 2002;Gritz et al 1975;Isbell and Vogel 1949;Soyka et al 2008;Verdejo et al 2005;Hilsabeck et al 2002;Mintzer and Stitzer 2002;Ornstein et al 2000;Prosser et al 2006;Veldhuijzen et al 2006).…”
Section: Introductionmentioning
confidence: 99%